2016
DOI: 10.1259/bjr.20160321
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between extracranial venous abnormalities and multiple sclerosis: a quantitative MRI study

Abstract: Sirio Cocozza and Antonietta Canna contributed equally to this work. Giuseppe Palma and Enrico Tedeschi share senior authorship.Objective: We aimed to evaluate the presence of venous stenosis and blood flow abnormalities in the neck vessels of patients with multiple sclerosis (MS), in respect to a group of age-and sex-matched healthy controls (HC), and their possible relations with clinical variables using a semi-automated quantitative MRI method. Methods: 45 patients with relapsing remitting MS and 40 HC were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…14, 16 On the other hand, some other studies reported absence of significant differences between MS and HC as to IJV CSA and flow rates. 15, 36 Our results at baseline are in line with the latter group of findings. However, the IJV CSA changes that we observed longitudinally in this study, in MS patients, may suggest a potential link between IJV CSA and the disease course.…”
Section: Discussionsupporting
confidence: 91%
“…14, 16 On the other hand, some other studies reported absence of significant differences between MS and HC as to IJV CSA and flow rates. 15, 36 Our results at baseline are in line with the latter group of findings. However, the IJV CSA changes that we observed longitudinally in this study, in MS patients, may suggest a potential link between IJV CSA and the disease course.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the anisotropic resolution of 2D PC voxels might theoretically have introduced a slightly imprecise velocity measurement with regard to curved vessel segments. In accordance with the approach of other groups, we chose straight vessel segments for the positioning of all vessel segments, minimizing the influence of this theoretical limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies examined the morphologic aspects of the venous system obtained by magnetic resonance imaging (MRI) or digital subtraction venography, which might be less susceptible to methodological bias, yet represent static observations. Several studies in MS patients have performed functional assessments of venous hemodynamics by means of MRI . Although the juxta‐ and subcortical white matter of the cerebral hemispheres' convexity is a frequent location of MS plaques and the superior sagittal sinus represents the main drainage, a systematic, concomitant hemodynamic assessment of both the superficial and deep intracranial venous system in MS, respecting the possible influx of collaterals into the superior sagittal sinus, is hitherto lacking.…”
Section: Fisher's Exact Test Regarding the Distribution Of Ccsvi Critmentioning
confidence: 99%
“…In this single-center observational study, 77 patients with MS (52 RRMS and 25 PMS according to the 2013 revised definition of MS phenotypes 20 ) and 41 healthy controls (HC) were enrolled from October 2013 to July 2015 in a neuroimaging study of neuroinflammatory disorders. 21,22 All patients with MS fulfilled the 2010 revised McDonald criteria, 23 while none of the HC presented with any condition that could affect the CNS. For all patients, the Expanded Disability Status Scale (EDSS) score was determined within 1 week from MR imaging by an experienced neurologist as an index of clinical disability, along with the record of disease duration (DD) and disease-modifying treatment (DMT) type (On-line Table 1).…”
Section: Subjectsmentioning
confidence: 99%